Utilization of podcasts as learning media at Muhammadiyah elementary school Al-Mujahidin, Wonosari, Gunung Kidul - Junaedi, Fajar; Sukmono, Filosa Gita (Universitas Muhammadiyah Magelang, 2021)
During the Covid-19 pandemic, face-to-face learning activities in schools had to stop. The problem faced by Muhammadiyah elementary school Al-Mujahidin Wonosari, Gunungkidul is that there is no audio-based learning media available online. To overcome this problem, the activities carried out are to train teachers to master the competence of educational podcast production. Media that is auditive, attracts the interest of the younger generation, and is easy to produce is the advantage of podcasts. Service activities were carried out through workshops and educational podcast production practices using the Anchor.fm application. At the end of this activity, it was revealed that the teachers were able to master the production of podcasts for learning media.